Degeneration and regeneration of the intervertebral disc: lessons from development - Lachlan J. Smith; Nandan L. Nerurkar; Kyung-Suk Choi; Brian D. Harfe; Dawn M. Elliott (The Company of Biologists, 2011)
Degeneration of the intervertebral discs, a process characterized by a cascade of cellular, biochemical, structural and functional changes, is strongly implicated as a cause of low back pain. Current treatment strategies for disc degeneration typically address the symptoms of low back pain without treating the underlying cause or restoring mechanical function. A more in-depth understanding of disc degeneration, as well as opportunities for therapeutic intervention, can be obtained by considering aspects of intervertebral disc development. Development of the intervertebral disc involves the coalescence of several different cell types through highly orchestrated and complex molecular interactions. The resulting structures must function synergistically in an environment that is subjected to continuous mechanical perturbation throughout the life of an individual. Early postnatal changes, including altered cellularity, vascular regression and altered extracellular matrix composition, might set the disc on a slow course towards symptomatic degeneration. In this Perspective, we review the pathogenesis and treatment of intervertebral disc degeneration in the context of disc development. Within this scope, we examine how model systems have advanced our understanding of embryonic morphogenesis and associated molecular signaling pathways, in addition to the postnatal changes to the cellular, nutritional and mechanical microenvironment. We also discuss the current status of biological therapeutic strategies that promote disc regeneration and repair, and how lessons from development might provide clues for their refinement.